Staropolskie przekłady epiki w życiu literackim oświecenia: edytorzy wobec problemu starzenia się tekstów - Bajer, Michał (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article looks at the ways in which late Enlightenment and early Romantic editors handled Old Polish translations of epic poetry (primarily Tasso, Ariosto, and Virgil). Using editions by Minasowicz, Przybylski, Dmochowski, and Zawadzki as examples, it demonstrates various responses to changes in language and poetics: discreet modernizations, editions with extensive commentaries, treating old translations as “monuments” of literary history, and using them as starting points for new translations. The author connects publishing practices with the emergence of historical thinking about literature and with European debates on translation. Editing emerges as an important form of work on the literary canon and memory, allowing us to capture the dynamics of literary life in the 18th and early 19th centuries.